Walk the line: An ethical framework for interactions with law enforcement in trauma care environments. Issue 2 (18th February 2023) - Tatebe, Leah C.; Kaufman, Elinore J.; Nappi, Tina; Dennis, Andrew J.; Neely, Kathy J.; Hall, Erin C.; Smith, Michael; Duncan, Thomas
Abstract : Walk the Line: An Ethical Framework for Interactions with Law Enforcement in Trauma Care Environments. @traumadoctors Injury Prevention committee address ethical interactions with LEOs & provide recommendations to promote collaborative patient-centered care. Abstract :